2015
DOI: 10.1038/onc.2015.349
|View full text |Cite
|
Sign up to set email alerts
|

USP4 inhibits p53 and NF-κB through deubiquitinating and stabilizing HDAC2

Abstract: Histone deacetylases (HDACs) are major epigenetic modulators involved in a broad spectrum of human diseases including cancers. As HDACs are promising targets of cancer therapy, it is important to understand the mechanisms of HDAC regulation. In this study, we show that ubiquitin-specific peptidase 4 (USP4) interacts directly with and deubiquitinates HDAC2, leading to the stabilization of HDAC2. Accumulation of HDAC2 in USP4-overexpression cells leads to compromised p53 acetylation as well as crippled p53 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 52 publications
(70 reference statements)
3
54
1
Order By: Relevance
“…Meanwhile, the pro‐apoptotic protein Bax was significantly increased, whereas the anti‐apoptotic protein Bcl2 decreased, both of which are canonical downstream genes of p53, indicating that the activation of p53 signalling was involved in the regulatory effect of USP4 on cell apoptosis. However, recent studies revealed that USP4 antagonized p53 activation by regulating its acetylation or ubiquitination modification without prominent influence on its mRNA level,15, 18 which is different from our results. The underlying mechanism needs to be further investigated.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the pro‐apoptotic protein Bax was significantly increased, whereas the anti‐apoptotic protein Bcl2 decreased, both of which are canonical downstream genes of p53, indicating that the activation of p53 signalling was involved in the regulatory effect of USP4 on cell apoptosis. However, recent studies revealed that USP4 antagonized p53 activation by regulating its acetylation or ubiquitination modification without prominent influence on its mRNA level,15, 18 which is different from our results. The underlying mechanism needs to be further investigated.…”
Section: Discussioncontrasting
confidence: 99%
“…The endogenous USP4 could confer resistance to DNA damage agent by promoting DNA double‐stranded break (DSB) repair, resection and homologous recombination, whereas the knockdown of USP4 expression in U20S cancer cell significantly increased apoptotic cells in response to etoposide‐induced DNA damage 15. In line with these studies, our results also found that up‐regulated USP4 expression in melanoma mediated intrinsic tolerance to DNA damage agent cisplatin, further confirming the essential role of USP4 in DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HCC, USP4 facilitates tumor development via deubiquitylation and cyclophilin A stabilization . Studies also indicate that USP4 targets histone deacetylase 2 (HDAC2) to downregulate TNFα‐induced NF‐κB activation and suppresses p53 . Consistently, in breast cancer, has been shown to be dispensable for AKT‐induced breast cancer cell migration by linking AKT signaling to transforming growth factor‐beta (TGF‐β) signaling .…”
Section: Discussionmentioning
confidence: 98%
“…USP4 is an attractive DUB involved in a variety of cellular mechanisms. Furthermore, USP4 has important roles in DNA-end resection and DNA repair [4], p53 and NF-jB signalling [59], homologous recombination [60] and DNA double-strand breaks [61]. Therefore, USP4 is related to different aspects of cancer as an indispensable DUB by regulating cellular signalling.…”
Section: Discussionmentioning
confidence: 99%